The Umma in Italy: Eurocentric Pluralism, Local Legislation, Courts' Decisions. How to Make the Right to Worship Real - Anello, Giancarlo (Journal of Muslims in Europe, 2020)
The article describes the making of the right of worship of Muslim minorities in Europe and its current difficulties, presenting and commenting on the emblematic example of local legislation concerning the building of new mosques in northern Italy. Controlling norms arise from recent decisions of the Italian Constitutional Court. The Court declared unconstitutional certain provisions of two regional laws approved by the Lombardy region (2/2015) and the Veneto region (12/2016), which imposed very strict conditions for the opening, approval and use of mosques. In particular, the Court declared unconstitutional norms that—with regard to the building of places of worship—introduced certain conditions for groups with an agreement with the State and different conditions for those without. Moreover, the Court declared unconstitutional the principle that all religious services that take place in a building open to public should be conducted in Italian. The basic assumption of the article is that current discrimination is the combined result of anti-migration sentiment and Islamophobic prejudices, and the consequence of the Eurocentric nature of the principle of religious freedom. A historically-oriented pluralism and multilevel (national) enforcement of freedom of religion seem to be huge obstacles to the implementation of the right to worship for Muslims in Europe and Italy.